The size of the area affected by earthquake induced rockfalls: Comparison of the 1998 Krn Mountains (NW Slovenia) earthquake (Mw 5.6) with worldwide data - Gosar, Andrej (Acta geographica Slovenica, 2019)
The 1998 Krn Mountains Mw 5.6 earthquake had widespread effects on the natural environment, among which rockfalls prevail. All rockfalls were evaluated to estimate the total affected area. The 180 km2 area (r=7.6 km) was established and compared with two worldwide datasets. The affected area is considerably below the upper bound limit established from both datasets. The same is valid for the nearby 1976 Friuli Mw 6.4 earthquake with a 2050 km2 affected area. However, comparison with the ESI 2007 scale definitions has shown that the area affected by the 1998 Imax VII–VIII event is significantly larger than the one proposed by this scale, but smaller for the 1976 Imax X event. This could not be explained by differences in hypocentral depth or focal mechanisms of both events. The results of the study have implications for seismic hazard assessment and for understanding environmental effects caused by moderate earthquakes in mountain regions.